Low back pain functional disability in athletes: Conceptualization and initial development of a questionnaire - Zamani, E.; Kordi, R.; Nourian, R.; Noorian, N.; Memari, A. H.; Shariati, M. (Asian Journal of Sports Medicine, 2014)
Background: Low Back Pain (LBP) is one of the most prevalent causes of disability not only in the general population but also in athletes. Despite a large number of self-reported back specific disability questionnaires, there is no specific, well documented, outcome measure for athletes suffering from back pain.